The impact of non-caloric artificial sweetener aspartame on female reproductive system in mice model - Ab Qayoom Naik; Tabassum Zafar; Vinoy K Shrivastava (BMC, 2023)
Abstract Background Artificial sweeteners, used as sugar substitutes have found their ways into almost all the food items due to the notion that they are non-caloric. Aspartame is used in numerous food products throughout the world. The primary users of aspartame include diabetics and calorie conscious people who intend to limit their calorie intake. Methods Female Swiss albino mice were divided into three groups (12 mice each) for the duration of 30 and 60 days consecutively. The treatment groups received 40 mg/kg b. w. aspartame orally. Hormone assays using ELISA and tissue histopathology have been performed along with the fertility assay to access the treatment outcomeon the fertility of treated mice in comparison to controls. Results Present study reports that female mice treated with aspartame for 30 and 60 days showed significant reduction in body weight, relative organ weight of (liver and kidney) and gonadosomatic index. These changes were more significantly recorded in 60 days treatment group. Aspartame treated animals for 30 and 60 days showed duration-dependent decrease gonandotropins (follicle stimulating hormone and luteinizing hormone), and steroids (estradiol and progesterone). Moreover, severe histopathological changes, reduction in number of growing follicles, degenerative changes in follicular structure, corona radiata and zonagranulosa were also observed. Besides, histomorphological changes were also observed in the uterine structure including atrophic uterine endometrial glands, contracted endometrial lining, disruption of the endometrial structure and the shapes of blood vessels were also altered. Conclusion Non-nutritive artificial sweeteners including aspartame negatively impact the function of ovaries and feedback mechanism of reproductive hormones by affecting the hypothalamic-pituitary-gonadal axis. In light of present findings the aspartame negatively impacted the reproductive system of female mice. More studies are required to identify the molecular mechanism and the pathways involved.